PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMAHAMAN RELASIONAL SISWA SMP - Valentine Marheber; Tian Abdul Aziz; Lukman El Hakim (Universitas Insan Budi Utomo, 2024)
This type of study was quantitative with quasi-experimental method that aims to discover the effect of contextual teaching and learning (CTL) on students’ relational understanding ability and how much the effect is. This study was posttest only group control design. It was conducted at SMP Negeri in Tangerang. The sample of this study were choosen randomly by cluster random sampling technique, which is students of grade VIII. The experimental class consisted of 35 students that applied CTL approach, while the control class consisted 34 studensthat applied conventional study. Students’ relational understanding ability be measured with the test instrument that contain five essay questions of Pythagorean Theorem that has been tested valid and realiable. Based on the result of statistical hypothesis test using t-test, obtained that the average of students’ relational understanding ability that applied CTL approach is higher than the average of students’ relational understanding ability that applied conventional learning. This show that there is the effect of contextual teaching and learning approach on students’ relational understanding ability. As for the value of Cohen’s effect size, obtained is 69% that is included in medium category.